EFEKTIFITAS PEMBELAJARAN AKIDAH AKHLAK BERBASIS RUBELMU DI MTS MUHAMMADIYAH BANDAR LAMPUNG - Septa, Fadri; Basyar, Syaripudin; Zulhannan (Inspiratif Pendidikan, 2022)
This study aims to determine the effectiveness of RubelMu-based Akidah Akhlak learning at MTs Muhammadiyah Bandar Lampung. Learning effectiveness is the level of achievement of learning objectives so that it can bring positive results. RubelMu (Rumah Belajar Muhammadiyah) is a form of emergency curriculum to carry out learning during the Covid-19 pandemic. This research uses a qualitative approach with data collection methods of observation, interviews and documentation. The results of this study indicate that RubelMu-based moral creed learning at MTs Muhammadiyah Bandar Lampung can be said to be effective because of the advantages found during the implementation of moral creed learning through RubelMu, namely Learning through RubelMu can be done anywhere, students are also better able to understand the material, this is evidenced by the values of students' assignments which increase compared to face-to-face learning. Although in its implementation there are several obstacles related to unstable network connections, students can still carry out learning quite well.